2015
DOI: 10.2147/opth.s59725
|View full text |Cite|
|
Sign up to set email alerts
|

Potential role of lampalizumab for treatment of geographic atrophy

Abstract: The purpose of this article is to review the pathways underlying age-related macular degeneration and potential therapeutic targets, focusing on the complement pathway and the recent MAHALO Phase II trial of the investigational drug lampalizumab. This trial was the first to have shown positive results for the treatment of geographic atrophy in age-related macular degeneration. It has potential as a future treatment, and is currently undergoing a Phase III trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Our observations may have important implications in future management of nAMD. Complement inhibitors are currently in clinical trials for AMD [ 23 , 24 ], and the identification of suitable patients is important for the success of this type of immune therapy. Our results provide evidence that nAMD patients with CNV and with subretinal fibrosis may benefit more from the complement inhibitor therapy compared to other subgroups of nAMD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations may have important implications in future management of nAMD. Complement inhibitors are currently in clinical trials for AMD [ 23 , 24 ], and the identification of suitable patients is important for the success of this type of immune therapy. Our results provide evidence that nAMD patients with CNV and with subretinal fibrosis may benefit more from the complement inhibitor therapy compared to other subgroups of nAMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that uncontrolled or dysregulated complement activation may contribute to macular lesion development in AMD, which offers the opportunities for complement-targeted immune therapy. Indeed a number of complement inhibitors are in phase I, II and III clinical trials for AMD [ 23 , 24 ]. In view of the diversity of AMD phenotype, it is likely that different immune mechanisms may be involved in different types of AMD, and this is exemplified by the diverse response to anti-VEGF therapy observed in various clinical studies [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… 99 The 18-month Phase II MAHALO study assessed the efficacy of monthly intravitreal injections of lampalizumab in halting the progression of GA in patients with bilateral disease. 100 Lampalizumab (anti-factor D Fab) is a humanized monoclonal antibody (Fab fragment), which is a selective inhibitor of complement factor D ( CFD ). Using autofluorescence and color fundus photographs, it was found that patients had a 20% reduction in mean change from baseline in the GA area at month 18.…”
Section: Prophylaxis and Treatment Of Dry Amdmentioning
confidence: 99%
“…Currently, potential candidates, such as complement component inhibitors, antibody-based compounds, and receptor antagonists, are in clinical trials or in preclinical evaluation [ 179 ]. While eculizumab, a humanized IgG antibody against complement component 5 (C5), seems to be ineffective in the management of dry AMD patients [ 180 ], treatment with lampalizumab, an antibody that inhibits complement factor D, reduced the progression of geographic atrophy lesion [ 181 ]. Since treatment with lampalizumab seems to be more effective in patients with specific CFI genotypes, a phase III trial is currently running.…”
Section: Implications For Preventive and Personalized Medicinementioning
confidence: 99%